Sensitivity of polyphagous (Plodia interpunctella) and stenophagous (Ephestia kuehniella) storage moths to residual insecticides: effect of formulation and larval age - Stejskal, Vaclav; Stara, Jitka; Pekar, Stano; Nesvorna, Marta; Hubert, Jan (Insect science, 2021)
Pyralid moths, Ephestia kuehniella and Plodia interpunctella, are prevalent stored product pests. The insecticides are the main tool to control these moths in the stores. The data describing the response of these moths to insecticides are scarce. The lethal effect of the organophosphate, pyrethroid, and halogenated-pyrrole on moths larvae were compared in laboratory test. The hypothesis was that the very polyphagous P. interpunctella would have generally higher insecticide tolerance than that of the stenophagous E. kuehniella. Different insecticide concentrations were applied onto the inner surface of glass tube vials. Ten larvae of 14 or 21 d old of E. kuehniella and 7 or 14 d old of P. interpunctella were used by treatment. The larval mortality was checked after 24 h of exposure. The mortality was significantly influenced by age of larvae and the groups of chemicals. No differences among the efficacies of the tested formulations with identical active compounds were found, except significant different mortality of E. kuehniella on deltamethrin formulations. A comparison of analytical standards showed that P. interpunctella was less susceptible to the active ingredient pirimiphos-methyl than E. kuehniella, while E. kuehniella was less susceptible to deltamethrin than P. interpunctella. No differences between the two species were observed for chlorfenapyr. We therefore rejected the hypothesis that polyphagy/stenophagy can be a general predictor of insecticide tolerance in the two tested storage moths. The most important finding for effective use was that the young larvae of both species were more susceptible to tested insecticides than older larvae.
Keywords: můry; pesticides; IRAC; larva; Insect Control; insekticidy; Larva; Pyralidae; Insecticides; efficacy; integrated pest management; residual; zvířata; dezinsekce; Moths; Animals